2018
DOI: 10.1590/0100-29452018419
|View full text |Cite
|
Sign up to set email alerts
|

Mango dehydration: influence of osmotic pre-treatmentAnd addition of calcium chloride

Abstract: Mango (Mangifera indica L.) can be characterized as a greatly accepted fruit due to its sensory attributes of flavor and aroma. However, it has a large production during the harvest season and requires preservation through processing. Osmotic pretreatment, followed by drying, provides products with higher quality and stability. The present study explored the effects of osmotic pretreatment with and without addition of calcium chloride in the nutritional characteristics and sensorial acceptance of dehydrated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
2
4
0
2
Order By: Relevance
“…Another recent study from the same researchers (Sulistyawati et al, 2020) confirmed that applying VI, and to a lesser extent adding PME with calcium to the osmotic solution, decreased the sugar gain, but without increasing vitamin C loss of osmo‐dehydrated mangoes. In the same line of research, Sanjinez‐Argandona, Yahagi, Costa, and Giunco (2018)) found that using calcium chloride during osmotic dehydration of mango lower the sugar uptake due to the formation of calcium pectate which increases the cell stiffness thus reducing the mass transfer. Other scientific reports on the same subject found out that increasing the thickness of the product may reduce the sugar uptake, as observed during such is the case of the osmotic dehydration of statistical approach research done for mangoes (Madamba & Lopez, 2002) or kiwifruit (Cao, Zhang, Mujumdar, Du, & Sun, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Another recent study from the same researchers (Sulistyawati et al, 2020) confirmed that applying VI, and to a lesser extent adding PME with calcium to the osmotic solution, decreased the sugar gain, but without increasing vitamin C loss of osmo‐dehydrated mangoes. In the same line of research, Sanjinez‐Argandona, Yahagi, Costa, and Giunco (2018)) found that using calcium chloride during osmotic dehydration of mango lower the sugar uptake due to the formation of calcium pectate which increases the cell stiffness thus reducing the mass transfer. Other scientific reports on the same subject found out that increasing the thickness of the product may reduce the sugar uptake, as observed during such is the case of the osmotic dehydration of statistical approach research done for mangoes (Madamba & Lopez, 2002) or kiwifruit (Cao, Zhang, Mujumdar, Du, & Sun, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Several Studies have used different pre-treatments for the drying of various fruits and vegetables. Examples are lemon juice, salt solution, and hot water blanching for mango (Dereje and Abera, 2020); blanching for papaya (Nguyen et al, 2019); osmotic pre-treatment with and without addition of calcium chloride for mango (Sanjinez-argandoña et al, 2018); and ascorbic acid dip, honey dip and steam blanching for mango fruit (Adepoju and Osunde, 2017).…”
Section: *Corresponding Authormentioning
confidence: 99%
“…Therefore, the mangoes dried at 50 and 60 °C had the highest acceptance in the opinion of the tasters, without significant differences between these treatments for all attributes evaluated. Good acceptance was also verified by Sanjinez-Argandoña et al (2018) for the mango cv. Palmer cut into pieces and subjected to osmotic dehydration (sucrose solution at 60%; 40 ºC/2 hours) followed by convective drying at 50 ºC with air velocity of 1.6 m s -1 , obtaining acceptance level greater than 70% for color, odor, flavor, texture and overall appearance.…”
Section: Resultsmentioning
confidence: 73%